Intergenerational Language Transmission and Identity Formation among Minority Language Speakers in the Kei Islands, Indonesia - Litaay, Simona Christina Henderika; Rahawarin, Yunus (Jurnal Tahuri, 2023)
This study examines intergenerational language transmission and identity formation among minority language speakers in the Kei Islands, Eastern Indonesia, where the Kei language (Veveu Evav) is gradually marginalized by the increasing dominance of Bahasa Indonesia. Using a qualitative ethnographic approach, data were collected from three generational groups across ten families, alongside cultural leaders and teachers, through participant observation, semi-structured interviews, natural conversation recordings, and document analysis. The findings indicate that the Kei language remains strong in ritual and emotional domains but shows significant decline in educational and digital contexts. Parents act as linguistic mediators, balancing the preservation of traditional values with the practical demands of national language use. Younger speakers construct hybrid Kei identities through narratives, music, and online expressions, reflecting both local attachment and global aspiration. The study introduces the Intergenerational Identity Transmission Model (IITM), integrating intergenerational language transmission with identity formation, a linkage rarely explored in Indonesian sociolinguistics. This conceptual and empirical contribution broadens understanding of language socialization by incorporating online and interfaith dimensions, while providing insights for minority language revitalization and education policies that promote multilingual and culturally grounded identities.